Firing of Hippocampal Neurogliaform cells induces suppression of synaptic inhibition - Li, G (2014)
The hippocampus contains more than 21 types of inhibitory interneurons that express different proteins and innervate different sub-domains of pyramidal cells to regulate the spatiotemporal integration of excitatory postsynaptic potentials (EPSPs) and to define temporal windows for spiking. Neurogliaform cells (NGFCs), form synapses on the distal tufts of pyramidal cell apical dendrites alongside excitatory inputs from the entorhinal cortex. NGFCs express neuronal nitric oxide synthase (nNOS), are often synaptically coupled, and fire rhythmically during theta oscillations in vivo. In this thesis, I describe a novel form of synaptic communication between these interneuron types, hereafter referred to as the firing induced suppression of inhibition (FSI). Specifically, I found that when a theta-associated activity patterns were evoked in NGFCs from rodent hippocampal slices, the cells exhibited a transient reduction in unitary IPSP amplitude. My data suggest that FSI requires the backpropagation of action potentials, calcium influx through L-type calcium channels, nNOS activity within the dendrites of interneurons, and the activation of NO-sensitive guanylyl cyclase (NOsGC) receptors that are present on presynaptic terminals. My results also demonstrate the physiological impact of this phenomenon by showing that when FSI occurs, the strength of incoming excitatory postsynaptic potentials onto NGFCs are transiently sharpened. Specifically, FSI indirectly increased the amplitude of EPSPs. Thus FSI may enhance spatial and temporal summation of excitatory inputs to NGFCs and regulate their inhibition of pyramidal cells.